Air-assisted activation strategy for porous carbon spheres to give enhanced electrochemical performance. Issue 19 (5th February 2016) - Xuan, Huaqing; Wang, Yiliang; Lin, Gaoxin; Wang, Fan; Zhou, Lin; Dong, Xiaoping; Chen, Zhi
Abstract : Porous carbon spheres showing excellent pore structures and superior electrochemical performance were obtained from a resorcinol–formaldehyde resin by an air-assisted activation strategy. Abstract : The use of activated porous carbons in supercapacitors is of increasing interest as a result of their superior porosity and facile preparation. However, their porous structure is strongly dependent on the activation procedure. We report here an air-assisted approach to activate a spherical resorcinol–formaldehyde resin to obtain porous carbons without the use of an inert atmosphere or chemical activating agent. The porous structures of the obtained activated carbon spheres (AACSs) were related to the activation time and the percentage of mesopores gradually increased as the activation time increased to 6 h. The sample activated for 6 h (AACS-6) had the largest pore volume (1.01 cm g −1 ) and the highest Brunauer–Emmett–Teller surface area of 2178 m 2 g −1 . The optimum electrochemical performance was realized on an AACS-6 electrode that had a large specific capacitance of 222 F g −1 at 0.5 A g −1 in a three-electrode system. A slight decrease in capacitance (12.5%) was obtained as the current density increased to 20 A g −1, indicating the significant rate capability. The AACS-6 electrode showed excellent cycling stability with a ∼97% retention of the initial capacitance after 5000 cycles. The assembled symmetrical cell based on the AACS-6 electrode had a high energy density of 10.1 W h kg −1 at a power density of 398.7 W kg −1 in the potential range of 0–1.6 V in a 0.5 M Na2 SO4 aqueous electrolyte.